The Characteristics of Business Competition Procedural Law in Indonesia: An Analysis - Arif Wicaksono; Arief Budiono; Saslina Kamaruddin; Nadia Nabila Mohd Saufi; Faisal Faisal (Universitas Muhammadiyah Malang, 2026)
Business competition is an important element in the modern market economic system in Indonesia, functioning to achieve efficiency and innovation, as well as increase social welfare. However, the competition dynamics do not always operate in an ideal manner. Various market distortions, such as monopolies, cartels, tender control, and the abuse of dominant positions, still often happen, hindering the creation of an efficient market. The problem formulations of this paper are: (1) What are the basic characteristics of the business competition legal procedures? (2) How are they implemented? This research strives to answer basic questions on the characteristics and implementation of business competition legal procedures as applied by the Business Competition Supervisory Commission. This research utilized the normative-juridical research method with a focus on the study of positive legal norms, especially those which are applied by the Business Competition Supervisory Commission. The procedural law carried out by this commission has its own unique characteristics, which are sui generis, meaning that they do not fully follow the patterns of criminal and civil legal procedures. The Business Competition Supervisory Commission combines the legal and economic approaches to assess an action as a violation of business competition principles. Thus, the evidencing process not only focuses on the formal law aspect but also considers market dynamics, industrial structure, and economic impacts towards business actors and consumers. The application of the procedural law by the Business Competition Supervisory Commission shows a systematic process, starting from the investigation, initial examination, and up to the further examination processes. This process is rather effective in disclosing violation patterns, such as cartels, tender control, and the abuse of dominant positions. The Business Competition Supervisory Commission’s decisions in various cases shows this commission’s capability to comprehensively assess anti-competition behavior through profound economic analysis.